2002
DOI: 10.1038/nature00778
|View full text |Cite
|
Sign up to set email alerts
|

Host-induced epidemic spread of the cholera bacterium

Abstract: The factors that enhance the transmission of pathogens during epidemic spread are ill defined. Water-borne spread of the diarrhoeal disease cholera occurs rapidly in nature, whereas infection of human volunteers with bacteria grown in vitro is difficult in the absence of stomach acid buffering. It is unclear, however, whether stomach acidity is a principal factor contributing to epidemic spread. Here we report that characterization of Vibrio cholerae from human stools supports a model whereby human colonizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
378
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 485 publications
(394 citation statements)
references
References 17 publications
15
378
1
Order By: Relevance
“…14, 15 Our results show that the mobile working population (15-44 years of age) represented the greatest proportion of cases, strongly suggesting that the combination of a highly mobile infectious working population coming together in the overcrowded and unsanitary conditions found in markets significantly influenced the spread of cholera into the city through person to person transmission. [29][30][31] Our data are based on an estimated suburb population and we recognize that the estimates may not reflect the real figures during the epidemic. However we tried to take into account the natural average growth of the population in order to work with most realistic population estimates possible.…”
Section: Discussionmentioning
confidence: 99%
“…14, 15 Our results show that the mobile working population (15-44 years of age) represented the greatest proportion of cases, strongly suggesting that the combination of a highly mobile infectious working population coming together in the overcrowded and unsanitary conditions found in markets significantly influenced the spread of cholera into the city through person to person transmission. [29][30][31] Our data are based on an estimated suburb population and we recognize that the estimates may not reflect the real figures during the epidemic. However we tried to take into account the natural average growth of the population in order to work with most realistic population estimates possible.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the first genome-wide transcriptomic studies of several important bacterial pathogens such as Vibrio cholerae (Merrell et al, 2002), Borrelia burgdorferi (Revel et al, 2002), Chlamydia trachomatis (Belland et al, 2003), C. pneumonia (Maurer et al, 2007) and S. Typhimurium (Eriksson et al, 2003) were performed with the help of microarrays and revealed gene expression patterns that suggested strategies used by these microbes to adapt to their host cells. Likewise, tiling arrays were applied to both in vitro and in vivo grown Listeria monocytogenes (Toledo-Arana et al, 2009) and used to identify sRNAs or novel virulence genes in streptococci (Kumar et al, 2010;Perez et al, 2009;Zheng et al, 2011).…”
Section: Transcriptomics: Then and Nowmentioning
confidence: 99%
“…These genes are upregulated in response to physical and chemical signals that are encountered in the host environment. Other signals indicate that the bacterium has exited the host (Merrell et al 2002). Experiments with many pathogens involved in a wide variety of infections have shown that these infectionrelevant signals modulate the supercoiling of bacterial DNA, providing a background regulatory influence upon which the dedicated gene regulatory proteins operate.…”
Section: Dna Supercoiling Bacterial Evolution and Pathogenesismentioning
confidence: 99%